Dietary intake, physical activity and sedentary behavior and association with BMI during the transition to parenthood: a prospective dyadic study - Versele, Vickà; Stas, Lara; Aerenhouts, Dirk; Deliens, Tom; Matthys, Christophe; Gucciardo, Leonardo; Devlieger, Roland; Clarys, Peter; Bogaerts, Annick (Frontiers in Public Health, 2023)
Introduction Little is known on how diet, physical activity (PA) and sedentary behavior (SB) changes during pregnancy and after childbirth in primiparous couples. Moreover, it is unclear how potential behavioral changes are associated with changes in BMI. This study examined changes in diet, PA and SB, and their association with changes in BMI in couples transitioning to parenthood. Methods Dietary intake (FFQ), PA, SB (both Actigraph GT3X accelerometers) and BMI of women and men were assessed at 12 weeks of gestation, 6 weeks and 6 months postpartum. Data were analyzed using dyadic longitudinal data analyses techniques. Results In women, a decrease in fruit intake, an increase in alcohol intake, an increase of light-intensity PA, and a decrease in SB were observed from the beginning of pregnancy up to 6 months postpartum. Decreases in fruit intake between 6 weeks and 6 months postpartum was associated with increases in BMI. Men did not show significant dietary changes, while an increase in light-intensity PA and a decrease in moderate-to-vigorous PA (MVPA) was observed at 6 months postpartum when compared to 12 weeks of gestation. Paternal increases in “avoidance food group” intake were associated with increases in BMI between baseline and 6 weeks postpartum. No associations of changes in BMI and changes in PA and SB were found. Discussion Not only mothers but also fathers experienced unfavorable changes in lifestyle during the transition to parenthood, with impact on BMI changes. This highlights the need to monitor unhealthy changes in lifestyle and body weight in both parents when expecting a child and after childbirth. Clinical trial registration Clinicaltrials.gov, NCT03454958.